Measurement of the $t \bar{t}$ production cross section in the dilepton channel in pp collisions at $\sqrt{s}$ = 8 TeV - CMS collaboration (2210 authors); Hollar, Jonathan; Nayak, Aruna; Calpas, Betty; Bargassa, Pedrame; Beirão Da Cruz E Silva, Cristóvão; Faccioli, Pietro; Ferreira Parracho, Pedro Guilherme; Gallinaro, Michele; Nguyen, Federico; Rodrigues Antunes, Joao; Seixas, Joao; et al. (My University, 2014)
The top-antitop quark (t t-bar) production cross section is measured in proton-proton collisions at sqrt(s) = 8 TeV with the CMS experiment at the LHC, using a data sample corresponding to an integrated luminosity of 5.3 inverse femtobarns. The measurement is performed by analysing events with a pair of electrons or muons, or one electron and one muon, and at least two jets, one of which is identified as originating from hadronisation of a bottom quark. The measured cross section is 239 +/- 2 (stat.) +/- 11 (syst.) +/- 6 (lum.) pb, for an assumed top-quark mass of 172.5 GeV, in agreement with the prediction of the standard model.